MORMONISM AND PROTESTANTISM: A COMPARATIVE ANALYSIS - E. S. Elbakyan; N. V. Shaburov (Концепт: философия, религия, культура, 2018)
The article analyzes in detail the basics and sources of dogma, theological specificity, religious practice, organizational structures of the Church of Jesus Christ of Latter-day Saints and individual Protestant denominations. A comparative analysis of the two Christian denominations is carried out taking into account the conditions of their emergence and historical development. The main positions of ethical doctrines, in particular economic and labor, social doctrines of Mormons and Protestants, etc., are examined separately. The features common to both confessions are highlighted, as well as those features that are peculiar only to Mormonism and only Protestantism. The Church of Jesus Christ of Latter-day Saints is a Christian denomination despite its specificity, with a long history and a membership of more than 15 million followers in 165 countries of the world (including the post-Soviet space), having more than 30 thousand parishes, 16 thousand assembly houses and 160 temples; five more temples are under construction [Sitnikov, 2014: 17, 33, 32]. Mormonism proximity to Protestantism can be traced in the socially significant aspects of the doctrine — moral teaching, work ethic, religious motivation of social service, and in certain theological positions. At the same time, there are noticeable differences in dogma as well as and in cult practice and church organization.